Pengaruh Kualitas Produk, Brand Trust dan Electronic Word of Mouth Terhadap Keputusan Pembelian pada Produk Sunscreen Wardah Berkandungan 4-Methylbenzylidene Camphor (4-MBC) - Oktavianti, Ayu Nur Rahma; Sarah, Siti; Wijaya, Fanji (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The beauty industry is currently growing rapidly, especially among young people and adults ; many well-known companies are trying to compete in the midst of business development; skin care products, especially for facial skin, have made companies increasingly strict in creating various products according to consumer tastes. In the last five years, BPOM noted cosmetics grew by 20.6 percent. Based on the competition in the cosmetics business that occurs in the current market, consumers have their own considerations regarding product offerings, product quality, different brands, and prices. The quality and content of skincare ingredients that are safe to use is one of the considerations for consumers to use as facial care equipment. One of the brands currently experiencing competition is the Wardah brand in the sunscreen category. this study aims to determine the effect of product quality, brand trust, and electronic word of mouth on purchasing decisions on wardah sunscreen products containing 4-methylbenzylidene Champor. This type of research is descriptive quantitative—sampling techniques using nonprobability sampling techniques with purposive sampling. The population in this study were all people in Bandung City who had used wardah sunscreen containing 4-MBC. the sample used was 100 respondents, and the data collection technique used a Likert scale, which was distributed using Google Forms. The results of data analysis show that partial product quality significantly affects purchasing decisions, and electronic word of mouth has no significant effect on purchasing decisions on wardah sunscreen products containing 4-MBC.